PHYSICO CHEMICAL ANALYSIS OF WATER QUALITY OF GAURALA LAKE OF BHADRAWATI WITH RESPECT TO SEASONAL VARIATIONS D ISTRICT CHANDRAPUR, MAHARASHTRA, INDIA. - AYASHA TABBASUM M.L.; PRAVEENKUMAR NASARE (The Bioscan, 2025)
The present research analyses the physico chemical characteristics of Gaurala Lake in Bhadrawati, D ist. Chandrapur, Maharashtra, India. The Gaurala lake water sample was studied monthly and seasonally at five different sites (G1 G5) from September 2023 to August 2024. The water samples were examined for 22 different parameters of physico chemical like C olour, Water Temperature, Transparency, Atmospheric Temperature, Turbidity, Conductivity, Total Solids (TS), Total Soluble Solid (TSS), Dissolved Oxygen (DO), Total Dissolved Solid (TDS), Conductivity, Biological Oxygen Demand (BOD), pH, Free CO 2 , Total Ha rdness, Chemical Oxygen Demand (COD), Magnesium,Chloride, Total Phosphorous, Nitrate, Calcium, Sulphate and Total Alkalinity. The values of physico chemical analysis showed variation in different seasons. The physico chemical analysis is important to study the quality of water and to preserve the health and balance of both abiotic and biotic components of the aquatic environment. The study revealed that the fluctuation of physico chemical parameters is due to the change in water status during three different seasons.